Perempuan dan Hukum dalam Masyarakat Hukum Adat Lampung Sebatin - Zuhraini, Zuhraini (Universitas Islam Negeri Raden Intan Lampung, 2017)
The interpretation of the Qur'an is often disputed. The terms of custom, culture and ideology is not one thing that descends from the sky. It is shaped by humans and socialized from one generation to other. Biological determinism has also reinforced the view. In such situations, the differences, discrimination, and injustice resulting from mistakes in understanding and interpreting the universal doctrine, create injustices against women, including the women’s rights and position in Lampung Sebatin customary law community. This article discusses the rights and position of women in Lampung Sebatin customary law community and the form of injustice for women in the society. The conclusion shows that, firstly, women's rights and position in Lampang Sebatin customary law community are far from fair principles. Not fair either in marriage law or inheritance law. Second, the form of injustice for women in indigenous communities of Lampung Sebatin, from gender analysis is marginalization, penomorduaan and labeling, violence, and excessive workload.